Choriocapillaris Ischemia at the Leakage Point of Patients With Acute Central Serous Chorioretinopathy - Wang, Zuofen; Xin, Zhaoting; Yang, Jun; Lu, Huawen; Wang, Haiying; Zhu, Lin (Frontiers in Medicine, 2021)
Purpose To determine ischemia of choriocapillaris at the leakage point of patients with acute central serous chorioretinopathy (CSC) by optical coherence tomographic angiography (OCTA). Methods A retrospective study of 38 eyes of 38 acute CSC patients with spontaneous complete resolution of subretinal fluid (SRF) was conducted and patients were followed for 3 months. Fundus fluorescein angiography (FFA) and indocyanine green angiography (ICGA) were performed at baseline; best corrected visual acuity (BCVA) and OCTA were collected at baseline and follow-up visits. Age and refractive error matched control group consisted of 40 eyes of 40 healthy people. Results BCVA of patients was significantly improved at 1- and 3-month. At baseline, all eyes showed a decreased choriocapillaris vessel density. The mean vessel density of superficial choroid (VDSC) at the leakage point area was 44.18 ± 9.27, which increased to 54.31 ± 9.70 at 1-month (P < 0.001) and to 55.19 ± 6.46 at 3-month (P < 0.001). The mean vessel density ratio was 0.90 ± 0.16 at baseline, which increased to 0.96 ± 0.15 at 1-month (P = 0.037) and to 0.97 ± 0.08 at 3-month (P = 0.016). The highest VDSC of patients was lower than that of normal control (P < 0.001). Conclusions The VDSC at the leakage point of acute CSC patients was significantly thinner and regularly increased with the recovery process, which suggested that ischemia might be one of the initiating factors in the pathogenesis of acute CSC.